Development of Techno-Pedagogical Skills among Teacher Educators: The Case of Higher Technical Teachers’ Training College of the University of Buea, Cameroon - Ngale Lyonga, Ngemunang Agnes; Nkeng, Asobo Jackson (Innovare Journal of Education, 2022)
The aim of this study was to investigate teachers’ perception of techno-pedagogical skills in HTTTC Kumba. It was hypothesized that the perceived usefulness of techno pedagogical skills has no significant effect on teachers’ performance in HTTTC Kumba. 42 teachers of HTTTC were sampled by multistage sampling technique and administered a questionnaire. The data were analyzed using frequencies and percentages for descriptive statistics, while the Chi-Square Test was used for testing the hypothesis. The results indicated a significant positive perception of technology among teachers in HTTTC Kumba despite the limitations and non-acceptance of technology demonstrated by some teachers in their responses. It was recommended that the teachers and teachers in training could be encouraged to have a more positive attitude towards the use of technology in their classrooms by providing the right infrastructure and provision for them to get technology-related help when needed.